Multi-aspect testing and ranking inference to quantify dimorphism in the cytoarchitecture of cerebellum of male, female and intersex individuals: a model applied to bovine brains - L. Corain; E. Grisan; J.-M. Graïc; R. Carvajal-Schiaffino; B. Cozzi; A. Peruffo (Brain Structure and Function, 2020)
The dimorphism among male, female and freemartin intersex bovines, focusing on the vermal lobules VIII and IX, was analyzed using a novel data analytics approach to quantify morphometric differences in the cytoarchitecture of digitalized sections of the cerebellum. This methodology consists of multivariate and multi-aspect testing for cytoarchitecture-ranking, based on neuronal cell complexity among populations defined by factors, such as sex, age or pathology. In this context, we computed a set of shape descriptors of the neural cell morphology, categorized them into three domains named size, regularity and density, respectively. The output and results of our methodology are multivariate in nature, allowing an in-depth analysis of the cytoarchitectonic organization and morphology of cells. Interestingly, the Purkinje neurons and the underlying granule cells revealed the same morphological pattern: female possessed larger, denser and more irregular neurons than males. In the Freemartin, Purkinje neurons showed an intermediate setting between males and females, while the granule cells were the largest, most regular and dense. This methodology could be a powerful instrument to carry out morphometric analysis providing robust bases for objective tissue screening, especially in the field of neurodegenerative pathologies.

Erratum to: The laminar organization of the motor cortex in monodactylous mammals: a comparative assessment based on horse, chimpanzee, and macaque - Bruno Cozzi; Andrea De Giorgio; A. Peruffo; S. Montelli; M. Panin; C. Bombardi; A. Grandis; A. Pirone; P. Zambenedetti; L. Corain; Alberto Granato (Brain Structure and Function, 2017)

The laminar organization of the motor cortex in monodactylous mammals: a comparative assessment based on horse, chimpanzee, and macaque - Bruno Cozzi; Alberto De Giorgio; A. Peruffo; S. Montelli; M. Panin; C. Bombardi; A. Grandis; A. Pirone; P. Zambenedetti; L. Corain; Alberto Granato (Brain Structure and Function, 2017)

Gene expression profiles of estrogen receptors α and β in the fetal bovine hypothalamus and immunohistochemical characterization during development - M. Panin; L. Corain; S. Montelli; B. Cozzi; A. Peruffo (Cell and Tissue Research, 2015)